2006
DOI: 10.1007/s00775-006-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-state-dependent reactions of cytochrome c with the trioxidocarbonate(•1−) radical: a pulse radiolysis study

Abstract: The reaction of the trioxidocarbonate(*1-) radical (CO (3) (*-) , "carbonate radical anion") with cytochrome c was studied by pulse radiolysis at alkaline pH and room temperature. With iron(III) cytochrome c, CO (3) (*-) reacts with the protein moiety with rate constants of (5.1 +/- 0.6) x 10(7) M(-1) s(-1) (pH 8.4, I approximately 0.27 M) and (1.0 +/- 0.2) x 10(8) M(-1) s(-1) (pH 10, I = 0.5 M). The absorption spectrum of the haem moiety was not changed, thus, amino acid radicals produced on the protein do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(52 reference statements)
2
7
1
Order By: Relevance
“…In the case of cytochrome c (in its ferric form), we confirmed the results obtained earlier by Domazou and Koppenol [8]. It has also been shown that CO 3…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the case of cytochrome c (in its ferric form), we confirmed the results obtained earlier by Domazou and Koppenol [8]. It has also been shown that CO 3…”
Section: Discussionsupporting
confidence: 92%
“…•-measured at pH 10 agrees perfectly with that observed by Domazou and Koppenol [8]. However, the same authors have found that the value of the rate constant of this reaction at pH 8.4 is lower and equals 5.1 9 10 7 M -1 s -1 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations